The Effect of "journey to literature survey and review" training on the research competencies of master students - Ormancı, Ümmühan (Journal of Turkish Science Education, 2024)
In order to carry out effective research, Master’s degree students are expected to have a good command of the literature. They need to know how to carry out a literature review and how to synthesise the studies found as a result of the review and turn them into an article if desired. As the shortcomings made at this stage will affect the whole process of research, students should be given the necessary training. This study aims to examine the effect of “Journey to Literature Survey and Review” training on Master's degree students' research competencies. An embedded mixed methods design was used in this study. The study is part of the "Journey to Literature Survey and Review" project conducted under the TUBITAK 2237-A Grant Program for Scientific Training. The study group of the research was determined using the purposive sampling method. The study group consisted of 33 Master’s degree students from different universities and education departments. In the training information on how to conduct a literature review and present the studies obtained was delivered theoretically and practically. The experimental implementation process was carried out in the form of 6-day and 8-hour daily training sessions. The training sessions provided detailed information on what a literature review is, how to search databases, and types of reviews. These sessions were conducted by 12 academics who are experts in their fields. The "Competence in Research Scale" and "Opinion Form" were used as data collection tools in the study. The results of the study showed that the research competencies of the students increased significantly with the application. Looking at the averages for the sub-dimensions, it is clear that there is a large increase in the literature review and methods dimensions in particular. In this context, it can be suggested to increase similar training on sub-dimensions that will improve research competencies.